Leadership in disruptive times. - Bawany, Sattar (Business Expert Press, 2020)
This book provides insights into an understanding of disruptive leadership. It explores the transformation of organizations in today's highly disruptive, increasingly VUCA, and digital-driven era of the Fourth Industrial Revolution (also known as Industry 4.0). It builds the case for organizations to revisit and, at times, reinvent their people strategy, internal systems and processes, and deploy the technologies that would suit disruptive times. The book also examines the attributes and competencies of disruptive leadership that would distinguish successful leaders as they guide their organizations through the disruption caused by the COVID-19 crisis and the digital transformation at the workplace.